2017
DOI: 10.1515/afe-2017-0125
|View full text |Cite
|
Sign up to set email alerts
|

TG/DTG/DTA, FTIR and GC/MS Studies of Oil Sand for Artistic and Precision Foundry with the Emission of Gases Assessment

Abstract: The paper presents the results of thermoanalytical studies by TG/DTG/DTA, FTIR and GC/MS for the oil sand used in art and precision foundry. On the basis of course of DTG and DTA curves the characteristic temperature points for thermal effects accompanying the thermal decomposition reactions were determined. This results were linked with structural changes occurred in sample. It has been shown that the highest weight loss of the sample at temperatures of about 320°C is associated with destruction of C-H bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The author, along with their team, has proposed an environmentally friendly method to reduce the final strength and improve the knock-out properties in molding or core sands. This is achieved by introducing a mineral material in the form of swelling aluminosilicate, specifically perlite ore. Research has demonstrated that the addition of perlite ore or ground vermiculite positively influences the reduction in the final strength and improvement in the knock-out properties [20,27]. Importantly, these additives do not adversely affect the mechanical and technological properties of the molding sands, the casting surface quality, or the ecological properties [28].…”
Section: Introductionmentioning
confidence: 99%
“…The author, along with their team, has proposed an environmentally friendly method to reduce the final strength and improve the knock-out properties in molding or core sands. This is achieved by introducing a mineral material in the form of swelling aluminosilicate, specifically perlite ore. Research has demonstrated that the addition of perlite ore or ground vermiculite positively influences the reduction in the final strength and improvement in the knock-out properties [20,27]. Importantly, these additives do not adversely affect the mechanical and technological properties of the molding sands, the casting surface quality, or the ecological properties [28].…”
Section: Introductionmentioning
confidence: 99%
“…Durability and time-regulated shelf life for molding; • High resistance-to-moisture during core storage; • High resistance-to-erosion and -penetration and no chemical interaction with the casting alloy; The problem of gas and the emission of odors is widely discussed in publications [3][4][5][6]. In this regard, molding and core sand systems based on organic binders should not be considered the most environmentally friendly due to the emission of BTEX group compounds, which is an indicator of the environmental harm of the molding sands.…”
Section: Introductionmentioning
confidence: 99%
“…Another solution [ 15 , 28 ] is conducting core production under vacuum conditions, which can help reduce the amount of gases emitted during the curing process and ultimately during the interaction with the high temperature of the liquid foundry metal. The emissions of materials used in casting production are gaining importance, as reflected in publications dedicated to monitoring the composition of gas products resulting from the thermal degradation of molding and core sands [ 29 , 30 , 31 , 32 ]. This stems from the need to reduce the negative impact on the natural environment, as well as the working environment [ 33 , 34 , 35 , 36 , 37 ], and it is achievable through the use of appropriate resin quality, selecting the proper 3D printing temperature, or even choosing the 3D printer model [ 38 ].…”
Section: Introductionmentioning
confidence: 99%